2014
DOI: 10.3354/meps10965
|View full text |Cite
|
Sign up to set email alerts
|

Trends, cycles, interannual variability for three pelagic species west of the Antarctic Peninsula 1993-2008

Abstract: The Palmer Long Term Ecological Research study region west of the Antarctic Peninsula is experiencing warming and changing seasonal sea ice dynamics. Abundance patterns of 3 species of pelagic secondary producers were analyzed for trends, cycles, range extensions or shifts in the location of highest density, and for changes in population dynamics over a 16 yr period (1993−2008). Species analyzed represented different hydrographic regimes and are known to have contrasting responses to seasonal sea ice dynamics:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 114 publications
4
56
1
1
Order By: Relevance
“…Larval krill abundance was estimated from the amount of larvae caught by the 1 m 2 net with 350 μ m mesh size. For evaluating the condition of larvae in terms of feeding activity (indicated by the digestive gland size), growth rate and stomach content, larvae were sampled in the OW and the MIZ with a RMT or a Bongo net 42 , whereas in the PIZ, larvae were sampled by scientific divers using the plankton pump system MASMA (MAnguera SubMArina) 9 . MASMA consists of a motor-driven centrifugal pump filtering seawater through a zooplankton net with 200 μ m mesh size into a 2 l cod end, which was located inside an airtight container.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larval krill abundance was estimated from the amount of larvae caught by the 1 m 2 net with 350 μ m mesh size. For evaluating the condition of larvae in terms of feeding activity (indicated by the digestive gland size), growth rate and stomach content, larvae were sampled in the OW and the MIZ with a RMT or a Bongo net 42 , whereas in the PIZ, larvae were sampled by scientific divers using the plankton pump system MASMA (MAnguera SubMArina) 9 . MASMA consists of a motor-driven centrifugal pump filtering seawater through a zooplankton net with 200 μ m mesh size into a 2 l cod end, which was located inside an airtight container.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…This implies that larvae have access to this high algal biomass within the sea ice. However, recent observations 9,10 indicate that the linkage between sea ice and krill recruitment success is not as direct as has been suggested. The timing of ice-edge advance and annual ice-season duration is highly variable, and does not necessarily show a clear link to krill recruitment in the following year ( Supplementary Figs.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Krill that over-wintered under the sea ice will have potentially remained in areas of open-ocean as the ice retreated. To be able to predict their distribution would require a dynamic representation of the sea ice field and of spring phytoplankton blooms that establish following its retreat, which are an important food source for krill and will affect their distribution in subsequent months Ross et al, 2014;Schmidt et al, 2014).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…They are important for nutrient cycling and carbon flux through the ecosystem (Laws 1977, Smetacek & Nicol 2005, and their massive biomass supports an important commercial fishery (Nicol et al 2012, Nicol & Foster 2016. A number of studies have shown a strong relationship between seasonal sea-ice extent and recruitment success of krill, emphasizing the importance of physical processes in winter (Loeb et al 1997, Atkinson et al 2004, Ross et al 2014, Saba et al 2014). In the last quarter of the 20th century, krill densities across the Southwest Atlantic sector of the Southern Ocean, near the Antarctic Peninsula, have reportedly declined between 36 and 80%, concomitant with declines in sea-ice extent and duration (Atkinson et al 2004).…”
Section: Introductionmentioning
confidence: 99%